The Independent Association of TSH and Free Triiodothyronine Levels With Lymphocyte Counts Among COVID-19 Patients - Lui, David Tak Wai; Lee, Chi Ho; Chow, Wing Sun; Lee, Alan Chun Hong; Tam, Anthony Raymond; Pang, Polly; Ho, Tip Yin; Cheung, Chloe Yu Yan; Fong, Carol Ho Yi; Law, Chun Yiu; To, Kelvin Kai Wang; Lam, Ching Wan; et al. (Frontiers in Endocrinology, 2022)
Background: Both lymphopenia and thyroid dysfunction are commonly observed among COVID-19 patients. Whether thyroid function independently correlates with lymphocyte counts (LYM) remains to be elucidated. Methods: We included consecutive adults without known thyroid disorder admitted to Queen Mary Hospital for COVID-19 from July 2020 to April 2021 who had thyroid-stimulating hormone (TSH), free thyroxine (fT4), free triiodothyronine (fT3) and LYM measured on admission. Results: A total of 541 patients were included. Median LYM was 1.22 x 109/L, with 36.0% of the cohort lymphopenic. 83 patients (15.4%) had abnormal thyroid function tests (TFTs), mostly non-thyroidal illness syndrome (NTIS). Patients with lymphopenia had lower TSH, fT4 and fT3 levels than those without. Multivariable stepwise linear regression analysis revealed that both TSH (standardized beta 0.160, p<0.001) and fT3 (standardized beta 0.094, p=0.023), but not fT4, remained independently correlated with LYM, in addition to age, SARS-CoV-2 viral load, C-reactive protein levels, coagulation profile, sodium levels and more severe clinical presentations. Among the 40 patients who had reassessment of TFTs and LYM after discharge, at a median of 9 days from admission, there were significant increases in TSH (p=0.031), fT3 (p<0.001) and LYM (p<0.001). Furthermore, patients who had both lymphopenia and NTIS were more likely to deteriorate compared to those who only had either one alone, and those without lymphopenia or NTIS (p for trend <0.001). Conclusion: TSH and fT3 levels showed independent positive correlations with LYM among COVID-19 patients, supporting the interaction between the hypothalamic-pituitary-thyroid axis and immune system in COVID-19.